2010
DOI: 10.1002/ana.21915
|View full text |Cite
|
Sign up to set email alerts
|

Dementia incidence continues to increase with age in the oldest old: The 90+ study

Abstract: Objective The oldest old are the fastest growing segment of the US population, and accurate estimates of dementia incidence in this group are crucial for healthcare planning. Although dementia incidence doubles every 5 years from ages 65 to 90 years, it is unknown if this exponential increase continues past age 90 years. Here, we estimate age- and sex-specific incidence rates of all-cause dementia in people aged 90 years and older, including estimates for centenarians. Methods Participants are from The 90+ S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
354
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 436 publications
(380 citation statements)
references
References 33 publications
17
354
0
9
Order By: Relevance
“…This is consistent with the increased prevalence and incidence of dementia in individuals age 85 or older. 29,30 Progression from normal cognition to MCI, or from normal to MCI to dementia, was not linear in 20% of the subjects, which has important implications for the study and diagnosis of MCI and dementia. First, only 1 of the unstable individuals was an APOE4 allele carrier, suggesting that the absence of the APOE4 allele may attenuate the rate of progression and decrease mortality.…”
Section: Discussionmentioning
confidence: 95%
“…This is consistent with the increased prevalence and incidence of dementia in individuals age 85 or older. 29,30 Progression from normal cognition to MCI, or from normal to MCI to dementia, was not linear in 20% of the subjects, which has important implications for the study and diagnosis of MCI and dementia. First, only 1 of the unstable individuals was an APOE4 allele carrier, suggesting that the absence of the APOE4 allele may attenuate the rate of progression and decrease mortality.…”
Section: Discussionmentioning
confidence: 95%
“…On the one hand, evidence linking certain comorbidities in heart failure to increased mortality [6][7][8][9][10] suggests that persons who survive to very old age with heart failure are less likely to have those comorbidities. On the other hand, the increase in prevalence with advancing age of several chronic diseases unrelated to heart failure, such as dementia [13][14][15][16] , suggests that older adults with heart failure may accumulate comorbidity as they survive into old age. An existing framework developed by Piette and Kerr (2006) characterizes comorbid conditions as either concordant with the primary disease-related in pathophysiology or management and on the same treatment pathway-or discor-dant with the primary disease-unrelated in pathophysiology or management and not likely to be part of the same treatment plan 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although the prevalence of Alzheimer disease (AD), Lewy bodies, and other brain pathologies appears to plateau in the tenth decade and beyond, 3 the risk of dementia continues to double with every 5 years of age reaching a staggering 40% per year in centenarians. 2 The causes of dementia and cognitive loss in extreme aging have been difficult to discern. Although AD continues to be the most frequent pathology in the oldest-old, many clinical pathologic studies have suggested a weakening of the association between dementia in this age group and individual pathologies including AD, vascular disease, and Lewy bodies.…”
mentioning
confidence: 99%